The Effect of Operating Cash Flow And Dividend Payout Ratio On Stock Returns of PT. Mayora Indah - Veronica, Meilin; Coyanda, John Roni (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
Dividend payments that tend to decline in food and beverage industry companies on the Indonesia Stock Exchange have an impact on company performance, which will be reported in the form of financial reports published annually. Financial reports have an important role in reducing the negative view of dividends in investment. This study aims to analyze the effect of operating cash flow and dividend payout ratio on stock returns at PT Mayora Indah Tbk for the period 2018–2021. The research method used is quantitative data with a population of 24 food and beverage subsector companies listed on the Indonesia Stock Exchange and a sample of 1 company with purposeful sampling analysis. The results of the study prove that operating cash flow has no significant effect on stock returns and dividend payout ratio has a significant effect on stock returns, and simultaneously, the operating cash flow and dividend payout ratio variables affect the stock returns of PT Mayora Indah Tbk for the period 2018–2021. This research is a material consideration and input for companies in carrying out policies that can affect stock returns in the company.